Efeitos vasculares e renais do Alpiste (Phalaris canariensis) em ratos normotensos e hipertensos - Passos, Clévia dos Santos [UNIFESP] (2010)
Hypertension is a disease highly prevalent throughout the world and it is associated with three chronic diseases namely; stroke, kidney disease, and heart disease. Popularly the birdseed Phalaris canariensis (Pc) has been used as an antihypertensive agent. The aim of this study was to evaluate the effect of the aqueous extract of Pc (AEPc) on arterial pressure and renal function of normotensive Wistar rats and spontaneously hypertensive rats (SHR). Also it was evaluated whether AEPc treatment would be able to prevent the development of hypertension in SHR, by administrating AEPc soon after weaning, i.e. before the establishment of hypertension. Methods: Adult male Wistar rats, SHR and young (3 weeks old) SHR were used. Adult animals were divided into groups control (receiving water) and treated with AEPc (100 mg/kg/day, p.o.) for 30 days. After this period treated group was divided into 2 sub-groups: treated for another 30 days (AEPc 60) and a group which AEPc treatment was interrupted and animals received only water for 30 days (AEPc 30). Young (three weeks old) and nonhypertensive SHR, received AEPc treatment during 30 days. Results: The administration of the AEPc for 60 days produced significant reduction in mean arterial pressure (MAP, mmHg) in both adult groups, Wistar (122±2 vs 103±4, p<0.05) and SHR (210±1 vs 171±, p<0.05). However, the interruption of treatment was followed by a gradual return of MAP to the baseline levels in both groups Wistar (117±1) and SHR (193±3). Young SHR group was normotensive after weaning (122±2) but became hypertensive after 30 (161±3) and 60 days (195±4). AEPc treatment during 30 and 60 days minimized the increase in MAP (133±2 and 148±4, respectively). The discontinuation of the treatment caused an increase in the MAP similar to observed in untreated group. There was no significant change in plasma parameters among groups. Fractional excretion of Na+ (FENa+) was lower in untreated SHR and AEPc treatment restored FENa+ to control levels. Conclusion: The results suggest that Pc has potential antihypertensive effect in SHR, without inducing any significant risk of nephrotoxicity and it may be use as an alternative and/or adjuvant treatment option to reduce blood pressure. The antihypertensive mechanism may be related by action of the biochemical constituents of Pc, mainly tryptophan and linoleic acid, precursors of the vasodilator aguds Kynurenine and prostaglandings respectively.